1981
DOI: 10.1159/000115271
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Velocity in the Human Supraorbital Nerve

Abstract: Maximal conduction velocity in the supraorbital nerve (afferent fibers for the blink reflex) has been estimated in 12 normal subjects (on the right and left side): the mean value was 41 m/s. Furthermore, this investigation was made on 23 patients with different pathologies (9 with trigeminal neuralgia with hypoesthesia, 8 with multiple sclerosis, 6 with cerebellopontine angle tumor). Normal and pathological results are discussed and diagnostic prospects of this procedure evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…The onset latency and amplitudes of the SNAPs from the STN and SONs were slightly, but not significantly, different on both the right and left sides and between females and males (Table ). In our study, the SCVs of both the SON‐s and SON‐d were lower than those reported by Therimadasamy et al and Cruccu et al, but similar to the results reported by Jandolo et al…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The onset latency and amplitudes of the SNAPs from the STN and SONs were slightly, but not significantly, different on both the right and left sides and between females and males (Table ). In our study, the SCVs of both the SON‐s and SON‐d were lower than those reported by Therimadasamy et al and Cruccu et al, but similar to the results reported by Jandolo et al…”
Section: Discussionsupporting
confidence: 91%
“…The onset latency and amplitudes of the SNAPs from the STN and SONs were slightly, but not significantly, different on both the right and left sides and between females and males ( Table 1). In our study, the SCVs of both the SON-s and SON-d were lower than those reported by Therimadasamy et al 26 and Cruccu et al, 22 but similar to the results reported by Jandolo et al 24 In our study, the amplitudes showed considerable variability, probably due to the varying terminal branches of the SONs and STN (Table 1). However, the intra-side and inter-side differences in amplitude were not significantly different.…”
Section: Snaps Of the Sons And Stnsupporting
confidence: 90%
See 1 more Smart Citation
“…Two previous studies employed the blink reflex to evaluate the conduction of the supraorbital nerve distal to the supraorbital foramen 6, 7. Using the blink reflex can have some limitations in the estimation of the peripheral supraorbital conduction.…”
Section: Discussionmentioning
confidence: 99%
“…The supraorbital nerve can be particularly affected by ion disturbances and hypersensitive to pain stimuli, as suggested by reports on the conduction velocity in the subraorbital nerve (17). The supraorbital nerve can be particularly affected by ion disturbances and hypersensitive to pain stimuli, as suggested by reports on the conduction velocity in the subraorbital nerve (17).…”
Section: Discussionmentioning
confidence: 98%